Accurate measurements of line strengths and air-broadening coefficients in methane around 1.66 µm using cavity ring down spectroscopy. (February 2019) - Kiseleva, M.; Mandon, J.; Persijn, S.; Harren, F.J.M.
Highlights: Line intensity in methane measured using cavity ring down spectroscopy. Line strength values for 12 CH4 lines around 1.66 µm determined with 1% accuracy. Line strength values for 13 CH4 lines around 1.66 µm determined with 2% accuracy. The values of the air-broadening coefficient for 12 CH4 and 13 CH4 lines are obtained. The results of data comparison are presented. Abstract: Accurate measurements of line strengths and air-broadening coefficients for 10 lines of 12 CH4 mostly from the band (2ν2  + ν3 ) and 2 lines of 13 CH4 from the band (2ν3 ) around 1.66 µm were performed using cavity ring down spectroscopy. Spectra of mixtures of 12 CH4 in air and 13 CH4 in air with well-defined mole fractions of methane were recorded at pressures between 10 and 90 mbar at 296 K. The values of the line strength for 12 CH4 and 13 CH4 lines were obtained with the uncertainty 1% and 2%, respectively. The uncertainties of the values of the air-broadening coefficient varied from 2 to 5% depending on the line. The values of the line strength and air-broadening coefficient for two methane isotopes obtained in this work were compared with the corresponding values from different experimental studies, as well as with the data given in HITRAN 2016 database.